"Patricia, Yvonne, Jim & me (K), father, Jim Sr., Ernestine, Ralph & Arthur" - Rorke Family (1935)
The Rorke, Forward and Pike families, in Ernest Forward's garden at Harbour Rock Hill, Carbonear. In the Title, "me" is Kathleen (Forward) Rorke and "father" is Ernest Edward Forward. Ernest Edward Forward (1859-1944), son of Capt. Mark William Forward and Mary (Bemister) Forward, was born at Carbonear on 29 May 1859. He married Tryphena Butt on 24 June 1885, and had three daughters: Ernestine (Forward) Pike, Hilda Samways (Forward) Pike and Kathleen (Forward) Rorke. Ernest Forward died on 14 April 1944. His daughter Ernestine (Forward) Pike (1887-1950), was born at Carbonear on 24 April 1887. She married Arthur S. Pike at Carbonear on 25 September 1913 and had 3 sons: Ernest Fletcher Pike (1914-1985), Arthur Pike Jr. (1916-1985) and Ralph Forward Pike (1924-1985). She died at Providence, Rhode Island on 22 March 1950. Ernest Forward's other daughter Kathleen (Forward) Rorke (1894-1979) was born at Carbonear on 1 June 1894. She married James Rorke, son of James Addy Rorke on 23 May 1917 and had three children: Patricia (Rorke) Yorke (1918-), James Ernest Rorke (1919-2005) and Yvonne (Rorke) Pratt (1922-1998). Kathleen died in 1979. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.